PROPHYLACTIC USE OF HEPARIN IN DIFFERENT SPECIALITY HOSPITALS IN SULAIMANI PROVINCE, KURDISTAN REGION - M. Ali, Kosar (European Scientific Journal, ESJ, 2014)
Objective: To determine the patterns of use of prophylactic heparin in different specialty hospital in Sulaimani province -Iraqi Kurdistan, in patients at risk of VTE, and compare it with international trends to establish a protocol or an algorithm to start using prophylactic heparin in our hospitals. Methods: This discriptive study was conducted from August 2011 to August 2012. Three hundred patients from three hospitals in Sulaimaniwere studied.The patient with high risk of thrombotic event (TE) selected from different specialities. No patients with heparin prophylaxis were excluded in the study.Data were collected according to special questioner form. The type of heparin used was unfractionated heparin. Results: Most of the patients in all three hospitals were female (58%, 100%, 61%), in General Medical hospital, Gynaecology hospital and Surgical hospital respectively. Most of the medical patients were above the age of 40 (71%), while In Gynaecology hospital 69% of patients were below 40 years. All of the patients in three different hospitals had risk factors; Surgical and Gynaecological patients had major risk factors by (80% and 82% respectively). Compared to international standards, heparin prophylaxis was under used in all three hospitals (21%, in medical, 18% in Gynaecology and 12% in surgical hospital). Conclusion: Despite the existence of comprehensive consensus guidelines for the prevention and treatment of VTE, thromboprophylaxis remains underused in our different speciality hospitals. Therefore, we need to improve thrombotic risk-assessment methods, familiarisation of clinicians with current best practice, and facilitation of appropriate prescribing of prophylaxis (establishing local hospitals guidelines).